Mathematic Resilience Ability of Students in Linear Program Material with Blanded Learning in the Era of Pandemic - Laelasari, Laelasari; Darhim, Darhim; Prabawanto, Sufyani (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
Mathematical resilience is a multidimensional construct in positive psychology focusing on mental health. The education system in Indonesia changed the 2019 Novel Coronavirus (COVID-19) pandemic. This pandemic event provides an opportunity for academics to take further academic decisions in the future. Good mathematical resilience skills are needed to prepare students to carry out the Tri Dharma of Higher Education. The purpose of this study is to comprehensively examine mathematical resilience skills using a blended learning model during a pandemic. This type of research uses case study research and is descriptive. The research was conducted on fourth-semester students of the 2020-2021 academic year at a private university in Cirebon, West Java, with research subjects consisting of 37 students. The data was obtained from a mathematical resilience questionnaire in linear program lectures using a blended learning model. Collecting data using a questionnaire instrument was analyzed using the formula for the distribution of frequencies and percentages. The results showed that students' mathematical resilience skills using blended learning in the Linear Program courses during the Covid-19 pandemic were good; previous research on the Linear Program courses obtained good results of resilience abilities but in different samples. The existence of the Covid-19 pandemic does not have much effect on mathematical resilience abilities.